Bats in urbanising landscapes: habitat selection and recommendations for a sustainable future. (January 2020) - Gili, Fabrizio; Newson, Stuart E.; Gillings, Simon; Chamberlain, Dan E.; Border, Jennifier A.
Abstract: Urbanisation is among the most ecologically damaging change in land use, posing significant threats to global biodiversity. Most bat species are threatened by urbanisation, although urban areas can also offer important roosting and foraging opportunities. Urban development should consider how bats are likely to respond to development, and take measures to minimise impacts. We used acoustic data from four years of citizen science monitoring (2013–2016) to quantify the importance of fine-scale habitat configuration and composition for bats in urban areas in eastern England. Bat distribution and activity were analysed in relation to remote sensing data representing impervious surface, waterbodies and tree-cover density. Furthermore, hypothetical future scenarios of urban development were considered, assuming an increase in impervious or woodland surface. Lakes and discontinuous woodland were the most selected habitats and urban areas were the least selected, with Barbastellus, Myotis and Plecotus species being the most vulnerable. Nyctalus, Pipistrellus and Eptesicus species were less influenced by the presence of urban areas. Our results suggest that urban growth should be sought through the expansion of existing urban blocks, rather than creating new urban patches, to minimise impacts on commuting or foraging sites. Creating bat-friendly habitat of an area at least equal to any new urban settlement could provide mitigation for negative effects of urbanisation. Opportunities to increase areas of discontinuous woodland should be encouraged, while preserving unmanaged areas within large plantations would likely support the exploitation of continuous woodland by bats. Highlights: Lakes and discontinuous woodlands are key habitats for most bat species. Barbastella, Myotis and Plecotus species are the most threatened by urbanisation. Urban growth should be sought through the expansion of already existing urban blocks. Increasing woodland areas together with urban areas may mitigate urbanisation impacts.